RBP4/Lp-PLA2/Netrin-1 signaling regulation of cognitive dysfunction in diabetic nephropathy complicated with silent cerebral infarction - Chen, Danyan; Huang, Xiaolong; Lu, Song; Deng, Huacong; Gan, Hua; Du, Xiaogang; Weixue, Tang (Experimental and Clinical Endocrinology & Diabetes, 2017)
Aim To investigate the RBP4/Lp-PLA2/Netrin-1 signal regulation of cognitive function impairment in diabetic nephropathy patients with silent cerebral infarction (SCI).Methods One-hundred patients newly diagnosed with diabetic nephropathy patients were included. The patients were divided into SCI group and NSCI group according to the radiological data. The degrees of cognitive dysfunction were evaluated. Serum RBP4 concentrations were determined by ELISA and protein expressions of Lp-PLA2 and Netrin-1 were determined by Western Blot.Results Compared with NSCI group, the cognitive function of patients in SCI group was impaired, the concentrations of RBP4 and the expressions of Lp-PLA2 and Netrin-1 increased (P<0.05). RBP4 concentrations were positively correlated with the cognitive dysfunction of SCI patients. Moreover, there existed a regression correlation between them.Conclusion RBP4 may be used as a predictive factor of diabetic nephropathy patients complicated with SCI and is positively correlated with cognitive dysfunction. RBP4/Lp-PLA2/Netrin-1 pathway activation may be one of the occurrence mechanisms in diabetic nephropathy complicated with SCI.
Keywords: diabetic nephropathy; silent cerebral infarction; function impairment; RBP4/Lp-PLA2/Netrin-1